(untitled) (Indian Journal of Arid Horticulture, 2025)
Precision agriculture (PA) is the use of mechatronics to control the fields’ temporal and spatial variability. Numerous elements, including appropriate planting, weeding and interculture, irrigation, insect and pest attacks, and harvesting methods, influence the output and quality of horticultural commodities. A proactive strategy that lowers some of the risks associated with these frequent horticultural and agricultural variables is precision agriculture. Producing high-quality, highly productive fruits in the fields requires the development of an exact and accurate autonomous production system, which frequently largely depends on human involvement. In arid regions, where water and arable land are limited, precision agriculture holds significant promise for enhancing the productivity and sustainability of fruit crops. Mechanization, precision farming, and agricultural transformation are three of these important technologies. Among these, precision and mechanical engineering are the foundations of a more all-encompassing system that makes use of automated technology. Accurate farming management is based on recognizing and adjusting to in-field variation. Some of the newest technologies used to assess and analyze agricultural and agricultural output disparities include robotic control systems for real-time weed detection and control, microcontroller-based variable rate herbicide/pesticide application systems, site-specific variable rate irrigation, wireless sensor network (WSN) enabled crop stress monitoring systems, RTK-GPS enabled seed planters or transplanters for geospatial mapping of row-crop plants/transplants, automated harvesting Sensors, satellites, aerial photography, Geographic Information Systems (GIS), and Global Positioning Systems (GPS).In order to manage water resources, choose the ideal harvesting site, balance fertilizer requirements, and forecast crop performance, sensor networks are crucial. In order to satisfy the requirements of certain regions and plants, accurate farming employs a set of extremely precise methods for technology users.